Aristotle on Moral and Economic Crises - Moutsopoulos, Yevangelos (Տիգրան Մեծ)
The 24 centuries that separate us from Aristotle despite the historical world changes that have occurred in the meantime, have by no means tarnished the value of his suggestions for to curing the ills that strike human societies.
Keywords: Social philosophy